2008
DOI: 10.2140/jomms.2008.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane stress and displacement for through-the-thickness cracks in plates of finite thickness

Abstract: The out-of-plane stress and displacement fields are investigated analytically for mode I through-thethickness cracks in an infinite plate of finite thickness within the first-order plate theory. The developed method is based on the distributed dislocation approach and an earlier derived three-dimensional solution for an edge dislocation. Numerical results are obtained through application of Gauss-Chebyshev quadrature for both finite length and semiinfinite crack cases. The calculated stress and displacement fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Numerical (e.g., Nakamura and Parks, 1989a,b;Nevalainen and Dodds, 1995;Leung and Su, 1995;Kwon and Sun, 2000;She and Guo, 2007;Harding et al, in press), analytical (e.g., Hartranft and Sih, 1970;Yang and Freund, 1985;Kotousov, 2007;Codrington et al, 2008;Kotousov et al, in press) and experimental (e.g., Humbert et al, 2000;Heyder et al, 2005) studies have suggested that the three-dimensional effects at sharp notches and cracks are confined within a close proximity to the notch tip and propagate to approximately one-half of the plate thickness from the notch tip in the plane directions. Consider a plane problem of a sharp notch in a plate of thickness 2 h when the zone of the three-dimensional stress state is fully encapsulated by the K-dominance zone, in which the classical plane stress solution is expected to be accurate.…”
Section: Large Plate With a Sharp Notchmentioning
confidence: 99%
“…Numerical (e.g., Nakamura and Parks, 1989a,b;Nevalainen and Dodds, 1995;Leung and Su, 1995;Kwon and Sun, 2000;She and Guo, 2007;Harding et al, in press), analytical (e.g., Hartranft and Sih, 1970;Yang and Freund, 1985;Kotousov, 2007;Codrington et al, 2008;Kotousov et al, in press) and experimental (e.g., Humbert et al, 2000;Heyder et al, 2005) studies have suggested that the three-dimensional effects at sharp notches and cracks are confined within a close proximity to the notch tip and propagate to approximately one-half of the plate thickness from the notch tip in the plane directions. Consider a plane problem of a sharp notch in a plate of thickness 2 h when the zone of the three-dimensional stress state is fully encapsulated by the K-dominance zone, in which the classical plane stress solution is expected to be accurate.…”
Section: Large Plate With a Sharp Notchmentioning
confidence: 99%
“…Most of the existing studies concerning the measurement of surface out-of-plane displacements near the crack tip in facture tests are only devoted to cases of small scale yielding in which the experimental data is correlated to analytical solutions based in the K dominant field and/or 3D FEM results [4,5,[9][10][11]. Moreover, almost all of the geometries of the specimens tested are not standard.…”
Section: Introductionmentioning
confidence: 99%